2016
DOI: 10.1021/acsnano.6b03238
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Driven Bioelimination of Magnetoplasmonic Nanoassemblies and Their Multimodal Imaging-Guided Tumor Photothermal Therapy

Abstract: Biocompatibility and bioelimination are basic requirements for systematically administered nanomaterials for biomedical purposes. Gold-based plasmonic nanomaterials have shown potential applications in photothermal cancer therapy. However, their inability to biodegrade has impeded practical biomedical application. In this study, a kind of bioeliminable magnetoplasmonic nanoassembly (MPNA), assembled from an Fe3O4 nanocluster and gold nanoshell, was elaborately designed for computed tomography, photoacoustic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 41 publications
(52 reference statements)
2
62
0
Order By: Relevance
“…Nowadays, the solvent thermal method can also be extended to the synthesis of magnetite-gold nanocomposites, as is now commonly carried out. Li et al utilised a solvothermal approach to synthesise Fe 3 O 4 nanoparticles in a single step-using FeCl 3 salts dissolved in gelatin in ethylene glycol with sodium acetate reacted at 200 • C for 6 h [49]. Gold seeds were prepared using chloroauric acid and tetrakis-hydroxymethylphophonium chloride (THPC), and seeded onto the gelatin coated Fe 3 O 4 nanoparticles through stirring.…”
Section: Solvothermal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the solvent thermal method can also be extended to the synthesis of magnetite-gold nanocomposites, as is now commonly carried out. Li et al utilised a solvothermal approach to synthesise Fe 3 O 4 nanoparticles in a single step-using FeCl 3 salts dissolved in gelatin in ethylene glycol with sodium acetate reacted at 200 • C for 6 h [49]. Gold seeds were prepared using chloroauric acid and tetrakis-hydroxymethylphophonium chloride (THPC), and seeded onto the gelatin coated Fe 3 O 4 nanoparticles through stirring.…”
Section: Solvothermal Methodsmentioning
confidence: 99%
“…This is of particular importance as gelatin can be readily degraded by a subclass of metalloproteinases in the body, which further ensures that the system is suitable for use in vivo [49]. The biocompatibility and bioelimination of this system was closely examined, and it was found that in the acidic tumour microenvironment the Fe 3 O 4 @Au nanoparticle assemblies were successfully broken in conjunction with the metalloproteinases.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…The good performance in tumor indicated that the nanocomplexes could passively target the tumor through enhanced permeability and retention effect during blood circulation. The high expression in liver may be caused by abundant resident macrophages in liver responsible for clearance of foreign matters from the body …”
Section: Resultsmentioning
confidence: 99%
“…Self-assembled nanostructures have emerged as efficient platforms for designing tumor-targeting epitopes 24, 25. Efforts have been made to create size-tunable and biodegradable self-assembled nanostructures that are responsive to endogenous stimuli (e.g., enzymes and changes in pH) 26-29.…”
Section: Introductionmentioning
confidence: 99%
“…For example, amphiphilic small molecules have been self-assembled into 95.4-nm-sized spherical nanoparticles that are then decomposed via ester hydrolysis that is catalyzed by cytoplasmic esterase 24. Nanoassemblies of iron oxide nanoclusters and gold nanoshells with gelatin in the size range of 205 nm were sensitive to pH and matrix metalloproteinases in tumor microenvironments and were bioeliminated from the body 25. Although assembling approaches of gold nanoparticles with different size and shapes have been reported 30-34, their ability to cross the BBB and brain tumor targeting mechanism studies have not yet been explored and are important to advance the field.…”
Section: Introductionmentioning
confidence: 99%